2021
DOI: 10.1155/2021/6634179
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Bacillus cereus Endophthalmitis: Clinical Characteristics and Antibiotic Susceptibilities

Abstract: Purpose. To report the clinical characteristics, antibiotic susceptibilities, and visual outcomes of patients with posttraumatic endophthalmitis caused by Bacillus cereus. Methods. In this retrospective, noncomparative case series, the medical records of eyes with culture-proven Bacillus cereus endophthalmitis treated from January 2016 to December 2019 at a referral center were reviewed. Clinical features, antibiotic susceptibilities, and visual outcomes were assessed. Results. A total of 19 eyes of 19 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…Intraocular injection of vancomycin and ceftazidime, combined with systemic administration of cefuroxime, cefazolin, or clindamycin, can reduce the rate of enucleation after trauma. 94 , 95 , 96 Systemic intravenous vancomycin combined with cefepime, tobramycin, or ofloxacin can reduce the incidence of post‐traumatic endophthalmitis. 97 It has been reported that hypersensitivity caused by intravitreal vancomycin may lead to haemorrhagic obstructive retinal vasculitis (HORV).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraocular injection of vancomycin and ceftazidime, combined with systemic administration of cefuroxime, cefazolin, or clindamycin, can reduce the rate of enucleation after trauma. 94 , 95 , 96 Systemic intravenous vancomycin combined with cefepime, tobramycin, or ofloxacin can reduce the incidence of post‐traumatic endophthalmitis. 97 It has been reported that hypersensitivity caused by intravitreal vancomycin may lead to haemorrhagic obstructive retinal vasculitis (HORV).…”
Section: Resultsmentioning
confidence: 99%
“…Combined vitreous injection of vancomycin and ceftazidime during surgical treatment has a certain effect on postoperative visual acuity improvement in patients with open globe injury and endophthalmitis. Intraocular injection of vancomycin and ceftazidime, combined with systemic administration of cefuroxime, cefazolin, or clindamycin, can reduce the rate of enucleation after trauma [94][95][96]. Systemic intravenous vancomycin combined with cefepime, tobramycin, or ofloxacin can reduce the incidence of post-traumatic endophthalmitis 97.…”
mentioning
confidence: 99%
“…We know that many variables, such as the course of disease, the virulence of microorganisms, the location of trauma, inflammation, injury degree of trauma, and retinal detachment, could influence FBCVA of PTBE. 4 , 32 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…For this reason, B. cereus s.l. is among the leading bacterial species that causes food poisoning outbreaks [ 1 ] and in certain severe cases, it can lead to endocarditis [ 4 ], endophthalmitis [ 5 ], and even death [ 6 , 7 , 8 ]. Regarding food products, B. cereus s.l.…”
Section: Introductionmentioning
confidence: 99%